Upaya Guru Meningkatkan Hasil Belajar Pendidikan Agama Islam menggunakan Metode Make A Match pada Siswa SD Negeri 2 Bengkulu Selatan - Sri Yulianti; Irwan Satria (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Effective learning is learning that is able to create learning processes and outcomes. It is clear that the learning process and learning outcomes of students are not only determined by the school, its pattern, structure, and curriculum content but are largely determined by the teacher's ability to teach in the classroom. This research is a class action research. This research was conducted at SDN 2 Bengkulu in 2023. The research subjects were fourth-grade students totaling 20 students. Data collection used observation, tests, and documentation. Researchers analyzed data using student learning completeness scores. The implementation of the research includes (1) planning; (2) action; (3) observation; and (4) reflection. The conclusion of the research shows that the make-a-match method can be used in order to improve the learning outcomes of Islamic religious education in elementary school students. For this reason, success in the learning process is influenced by the use of learning methods, one of which is the make-a-match learning method.